The Effect Of Islamic Work Ethics On Job Satisfaction In Organization; A Study In Sekolah Rendah Islam Indera Mahkota (Sri Abim), Kuantan - Qistina Balkis, Mohd Yusof; Nurus Saadah, Md Yusof; Rashidi, Abbas (Global Business and Social Entrepreneurship Resources, 2017)
Job satisfaction is one of the important elements that work to improve the performance and the achievement of an organization, especially school. This research aims to identify the contributions and the effects of Islamic Work Ethics on job satisfaction in organization and analyse the effectiveness level of Islamic Work Ethics on job satisfaction in organization. The sample for this study consisted of 27 teachers and school staff and they have to answer the questionnaire consists of 27 items. The data was analysed using SPSS (Statistical Package for Social Science) version 18 for Windows. Analytical results are expressed in terms of frequency and percentage statistic. The findings show that the implementation of Islamic work ethics in organization influenced job satisfaction among workers. For the purpose of further study in the future, researchers suggested that this study will use different methods and respondents.